B-Cell Receptor Signaling and Beyond: The Role of Igα (CD79a)/Igβ (CD79b) in Normal and Malignant B Cells - Tkachenko, Anton; Kupcova, Kristyna; Havranek, Ondrej (International journal of molecular sciences, 2023)
B-cell receptor (BCR) is a B cell hallmark surface complex regulating multiple cellular processes in normal as well as malignant B cells. Igα (CD79a)/Igβ (CD79b) are essential components of BCR that are indispensable for its functionality, signal initiation, and signal transduction. CD79a/CD79b-mediated BCR signaling is required for the survival of normal as well as malignant B cells via a wide signaling network. Recent studies identified the great complexity of this signaling network and revealed the emerging role of CD79a/CD79b in signal integration. In this review, we have focused on functional features of CD79a/CD79b, summarized signaling consequences of CD79a/CD79b post-translational modifications, and highlighted specifics of CD79a/CD79b interactions within BCR and related signaling cascades. We have reviewed the complex role of CD79a/CD79b in multiple aspects of normal B cell biology and how is the normal BCR signaling affected by lymphoid neoplasms associated CD79A/CD79B mutations. We have also summarized important unresolved questions and highlighted issues that remain to be explored for better understanding of CD79a/CD79b-mediated signal transduction and the eventual identification of additional therapeutically targetable BCR signaling vulnerabilities.
Keywords: mutace; CD79a; CLL; BCR signaling; LYN; lymphoid malignancies; CD79b; tonic BCR signaling; B lymphocytes; Mutation; signální transdukce; BTK; BCR; Signal Transduction; DLBCL; malignant B cells; Receptors, Antigen, B-Cell; kognice; BCR internalization; non-Hodgkin lymphoma; immunoglobulin; Cognition; ITAM; B cell development; receptory antigenů B-buněk; B-cell receptor; BCR assembly; buněčná membrána; NHL; antigen-induced BCR signaling; Cell Membrane